FENOMENA CYBERBULLYING PADA PEMAIN MOBILE LEGENDS PEREMPUAN - Adi Nugroho; Nurul Hasfi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2026)
This study examines the phenomenon of cyberbullying among female Mobile Legends players. The increasing participation of women in Mobile Legends: Bang Bang has also given rise to cyberbullying issues, which female players frequently experience. Various form of negative treatment, such as insults, teasing, gender discrimination, and sexualized comments, can impact their comfort and gaming experience. This study aims to identify the forms of cyberbullying experienced by female players and the factors that contribute to it in Mobile Legends. This study used a qualitative method with a phenomenological approach. Data were obtained through observation, in-depth interviews, and documentation with three informants who experienced cyberbullying while playing Mobile Legends. The results show that that cyberbullying experienced by female players is dominated by verbal insults, demeaning comments, gender discrimination, and verbal harassment. Factors triggering these actions include perceived poor gaming performance, high levels of competition in the game, and negative stereotypes against female players. The perceived impacts include feelings of sadness, anger, discomfort, and reduced interest in playing. This study concludes that cyberbullying against female players remains common and is influenced by a competitive culture and strong gender bias. Therefore, efforts are needed to create a safer and more inclusive gaming environment for all players.